2022
DOI: 10.33086/jhs.v15i02.2732
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Feeding Patterns And The Incidence Of Stunting In Children Aged 0-59 Months

Abstract: Stunting is one of the severe problems in Indonesia. One of its causes is a lack of nutritional intake during infancy. In addition, maternal parenting, especially in feeding patterns, will affect the children's growth and development. This study aims to determine the correlation between feeding patterns and the incidence of stunting. The research design used correlational analytics. The population was stunted children aged 0-59 months at Kalibuntu Village, Probolinggo Regency. In addition, there were 66 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…This study also revealed that parenting to eat in children under five is related to the incidence of stunting. This follows previous research which revealed that diet is associated with the incidence of stunting in children under five aged 0-59 months (Hidayati & Citra Dewi Pratiwi, 2022).…”
Section: Summary Of Evidencesupporting
confidence: 90%
See 1 more Smart Citation
“…This study also revealed that parenting to eat in children under five is related to the incidence of stunting. This follows previous research which revealed that diet is associated with the incidence of stunting in children under five aged 0-59 months (Hidayati & Citra Dewi Pratiwi, 2022).…”
Section: Summary Of Evidencesupporting
confidence: 90%
“…From the parenting perspective, this research is important to determine the incidence of stunting in toddlers aged 24-59 months. Good parenting patterns reduce stunting due to nutritional factors in feeding children who are increasingly optimal and good will affect the growth and development of children who are getting better (Hidayat, 2023). In addition, other studies have also revealed that the diet adopted by parents can influence food/energy intake, affecting children's growth (Abebe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a relatively low level of education can also affect awareness of proper nutrition for toddlers. However, there are also children from families with good socioeconomic status who experience stunting, although their numbers tend to be lower (Apriluana & Fikawati 2018, Hidayati & Citra 2022, Sholikhah & Dewi 2022.…”
Section: Causes Of Stunting In Rural Areasmentioning
confidence: 99%